2016
DOI: 10.2217/bmm-2016-0188
|View full text |Cite
|
Sign up to set email alerts
|

A New Inflammatory Marker for Bone Loss and Low Bone Mineral Density: Platelet-Tolymphocyte Ratio

Abstract: PLR level may predict low BMD with baseline measurement in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
2
28
1
1
Order By: Relevance
“…In our study, there was no significant relationship between low BMD and NLR in patients with hemophilia. Koseoglu et al [21] reported that PLR in postmenopausal women might be predictive of low BMD [21]. In this study, although the PLR was higher in hemophilic patients compared to controls, this result was not statistically significant.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In our study, there was no significant relationship between low BMD and NLR in patients with hemophilia. Koseoglu et al [21] reported that PLR in postmenopausal women might be predictive of low BMD [21]. In this study, although the PLR was higher in hemophilic patients compared to controls, this result was not statistically significant.…”
Section: Discussioncontrasting
confidence: 61%
“…We found no significant differences in CBC, ESR, CRP, liver and renal functions, ALP, Alb, P, total bilirubin, and fasting blood glucose between the two groups. A few studies reported an association of NLR, PLR, and MPV with osteoporosis [19][20][21][22]. However, no previous study evaluated the association between low BMD and NLR, PLR and MPV in hemophiliacs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in a cohort of postmenopausal women (N=211), PLR, but not platelet count or NLR, was significantly elevated in women with low bone mineral density (BMD) than in women with normal BMD ( P <0.05); PLR was also negatively correlated with femoral BMD (r=−0.21, P <0.002) [52]. A potential mechanism of the association between PLR and bone loss may be related to persistent systemic inflammation with impaired calcium transport and vitamin D metabolism, leading to osteoporosis and bone fractures [52]. Clinical implications of such a mechanism in postmenopausal women with and without chronic inflammatory diseases remain to be elucidated in specifically designed prospective studies.…”
Section: Plr In Neoplastic Prothrombotic and Metabolic Diseasesmentioning
confidence: 99%
“…The lower expression of the receptor also induced a worst response to vitamin D and a consequent increase in PTH levels [45]. In addition, evaluating postmenopausal OP patients, the PLT/lymphocyte ratio was found to correlate with low BMD [33,48], in particular in reference to the femoral and lumbar district [48], which is also related to low vitamin D levels, supporting the hypothesis that inflammation correlates with vitamin D levels [48]. The relationship between peripheral blood cell count and BMD in OP was investigated also by Kim et al which observed that PLTs count, as well as white and red blood cells counts, correlate with BMD in OP patients [43].…”
Section: Platelet Functions/features and Growth Factor In Plts In Ostmentioning
confidence: 99%